Experiencias generadas a partir del proyecto Orientación en Tiempos de Cuarentena: Un aporte para la Orientación en la virtualidad - Marin Solórzano, Andrea; Gómez Díaz, David; Masís Narváez, Elizabeth; Rivera Rojas, Emilio; Garro Núñez, Karen; Obando Castro, Margarita (Universidad de Costa Rica, 2021)
The article presents the systematization of the experiences of the beneficiary population and the volunteer students of the Guidance career generated from the Counseling in Quarantine Times (OETC) project. This project was developed by the Association of Guidance Students of the University of Costa Rica (ASEORI) during the months of March to August 2020. The objective was to demonstrate the contributions of the virtual accompaniment, provided from the Individual Counseling modality, through the experiences of the people involved in the project. This article is based on the theoretical-methodological model of systematization of experiences proposed by Oscar Jara, from a qualitative approach. In the project, from which the present systematization is derived, 23 volunteer students of the fourth year and bachelor's degree in Guidance participated, virtually accompanying 116 people from 56 different careers at the University of Costa Rica. The information was compiled through a database designed for the project. In it, informed consents, evaluations and self-evaluations made by the people involved were saved. The results demonstrate the effectiveness that can be achieved from Individual Guidance, complemented with the technological model for remote intervention, since it is shown that it is possible to carry out processes of accompaniment and counseling that promote the well-being of the people being counseled.